Entering a new era? The Impact of Corporate Tax Rates on Foreign Direct Investment with a BEPS Project Perspective - Andrésdóttir Kjerúlf,Ásthildur; Falkland,Maria (2024)
This thesis utilizes panel data from 38 OECD countries, spanning 21 years to estimate the impact of corporate income taxes on foreign direct investment. This analysis aims to examine how the relationship between these two variables has changed due to the launch of the Base Erosion and Profit Shifting (BEPS) project from the OECD/G20. Regressions are computed both for the full time period and three separate time periods, in order to analyze the possible BEPS project effect. The estimations from using the fixed effects method over the separate time periods give varying results. Notably, the period during the BEPS project always finds the relationship between statutory corporate taxes and foreign direct investment to be non-significant. The results for the full time period indicate that statutory corporate tax rates have a significant negative effect on foreign direct investment inflows, in line with previous empirical findings within the field.
Keywords: Foreign direct investment; corporate income taxes; BEPS; fixed effects estimator; panel data